A survey of Italian and Spanish neonatologists and paediatricians regarding awareness of the diagnosis of FAS and FASD and maternal ethanol use during pregnancy - Tarani L; Memo L; Falcon M; García-Algar O; Palmi I; Vagnarelli F; Spoletini R; Pacifici R; Mortali C; Pierantozzi A; Pichini S (BMC, 2011)
Abstract Background Ethanol is the most widely used drug in the world and a human teratogen whose consumption among women of childbearing age has been steadily increasing. There are no Italian or Spanish statistics on ethanol consumption during pregnancy nor any information regarding prevalence of fetal alcohol syndrome (FAS) and fetal alcohol spectrum disorders (FASD). There is also a reasonable suspicion that these two diseases are underdiagnosed by professionals from the above-reported countries. The objectives of this study were: 1) to evaluate the experience, knowledge and confidence of Italian and Spanish neonatologists and paediatricians with respect to the diagnosis of FAS and FASD, and 2) to evaluate professionals awareness of maternal drinking patterns during pregnancy. Methods A multiple-choice anonymous questionnaire was e-mailed to Italian neonatologists registered in the mailing list of the corresponding Society and administered to Italian and Spanish paediatricians during their National Congress. Results The response rate was 16% (63/400) for the Italian neonatologists of the National Society while a total of 152 Spanish and 41 Italian paediatricians agreed to complete the questionnaire during National Congress. Over 90% of the surveyed physicians declared that FAS is an identifiable syndrome and over 60% of them identified at least one of the most important features of FAS. Although over 60% Italian responders and around 80% Spanish responders were aware that ethanol use in pregnancy is dangerous, approximately 50% Italian responders and 40% Spanish ones allowed women to drink sometimes a glass of wine or beer during pregnancy. Neonatologists and paediatricians rated confidence in the ability to diagnosis FAS and FASD as low, with over 50% responders feeling they needed more information regarding FAS and FASD identification in newborn and child. Conclusions Italian and Spanish neonatologists and paediatricians do not feel confident about diagnosing FAS and FASD. More training is needed in order to accurately diagnose ethanol use during pregnancy and correctly inform pregnant women on the consequences on the newborn.